2007
DOI: 10.1021/jp068617b
|View full text |Cite
|
Sign up to set email alerts
|

Thin Film Amorphous Electrolytes:  Structure and Composition by Experimental and Simulated Infrared Spectra

Abstract: Ionic conducting glasses in thin film forms are promising candidates for applications in microelectronics devices such as microbatteries and microsupercapacitors. In recent years, it was shown that physicochemical properties of thin films may differ substantially from those of the target bulk materials. Thus, it remains a challenge in science and thin film technology to control the properties of thin films in terms of chemical composition and conditions of manufacturing. This work presents a structural investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…The infrared properties of the Si substrate are shown in Fig. 1͑b͒, as determined previously 16 and confirm its transparency in the infrared range. The bands observed in the k spectrum at 565, 608, 740, 815, 890, 965, 1302, and 1450 cm −1 originate from lattice modes of Si, 18 while the feature at 1107 cm −1 indicates oxygen impurities as arising from the asymmetric stretching vibration of Si-O-Si bridges.…”
Section: Spectral Simulationssupporting
confidence: 84%
See 2 more Smart Citations
“…The infrared properties of the Si substrate are shown in Fig. 1͑b͒, as determined previously 16 and confirm its transparency in the infrared range. The bands observed in the k spectrum at 565, 608, 740, 815, 890, 965, 1302, and 1450 cm −1 originate from lattice modes of Si, 18 while the feature at 1107 cm −1 indicates oxygen impurities as arising from the asymmetric stretching vibration of Si-O-Si bridges.…”
Section: Spectral Simulationssupporting
confidence: 84%
“…16. As it can be easily shown, the interference fringes due to the Si substrate used in this study ͑d 2 = 0.6 mm͒ have a period of approximately 2.5 cm −1 , and, thus, the Si interference pattern can be optically averaged by measuring low-resolution spectra ͑e.g., 10 cm −1 ͒.…”
Section: Spectral Simulationsmentioning
confidence: 81%
See 1 more Smart Citation
“…To this aim, we made use of a model based on rigorous expressions for transmittance of a film/substrate bilayer system which takes into full account all optical effects occurring in such a system. The model relevant to the present study is reported elsewhere [18][19][20].…”
Section: Characterisation Of Bulk Glasses and Films By Raman And Infrmentioning
confidence: 99%
“…2(a) and (b), respectively. As noticed in Section 2, the spectral comparison in the IR is based on a calculated transmittance spectrum which integrates all optical effects occurring in a bilayer system (film and substrate) [18][19][20]. Both figures demonstrate spectral variations between bulk glass and film.…”
Section: Structure Of Ge-sb-s Bulk Glasses and 2s1g Filmsmentioning
confidence: 99%